Penerapan Evidence Based Nursing Akupresur Pada Ibu Post Partum Dengan Produksi Air Susu Ibu (ASI) Tidak Maksimal - Annisa Hilmy Nurarifah (2022)
Breast milk is a white liquid that comes out of the mother's breast while the process of providing nutrition with breast milk is called breastfeeding. Infants who are exclusively breastfed in the data are only 44%. This is due to the position of the mother in breastfeeding, family support, and lack of stimulation to the breast. There is a non-pharmacological therapy that can be applied to suppress the production and stimulation of breast milk production that is called acupressure. Acupressure therapy is applied using acupoints ST15, ST16, and Li4. Stimulation at certain points in acupressure can signal the pituitary to regulate hormones and stimulate the hormones prolactin and oxytocin which play a role in breast milk production and milk secretion. The purpose of this case study is to determine the effect of giving acupressure to increase breast milk production. The method is carried out by giving acupressure therapy at the acupoints ST15,ST16, and LI4 for two session with each point being pressured for 30 seconds. The measuring instrument used for breast milk production is an observation sheet for mother and baby which consist of 16 statements with the interpretation of breast milk being smooth or not. Result: there is an increase in milk production experienced by post partum mothers after giving acupressure therapy at points ST 15, ST 16, and LI 4. Keywords : Acupressure , Breast-Feeding, Breast Milk, Post Partum.